Gender determination using dental arch characteristics among a south Indian pediatric population: A morphometric study - Girish Babu KL; Kavyashree Gururaj Hebbar (Arbu Academic Publishing, 2023)
Aim: To establish the normative data of dental arch characteristics and use them to determine the gender among a pediatric population of south India. Methods: Three hundred children aged 3 to 5 years were selected. The intra oral examination of each child was carried-out using a sterile disposable mouth mirror and a CPI probe. To receive maximum illumination, the oral examination was done in adequate natural daylight seating the child in upright positioning on a chair. Following, the molar and canine relationship was recorded. The investigators prepared the maxillary and mandibular impression of teeth and their dental casts. The intercanine width, intermolar width, dental arch form, arch length and arch perimeter was measured. The descriptive analysis of all the explanatory and outcome parameters was done using frequency and proportions for categorical variables, whereas in Mean & SD for continuous variables. To compare the selected dental arch parameters between genders, Independent Student t-test Chi-Square test were used. P≤0.05 was set as the level of significance. Results: The mesial step molar relationship and Class I canine relationship were found be more common among males compared to females, however it was statistically significant (p<0.26). Although, the ovoid arch form was commonly seen especially among males followed by square and tapered, it was not statistically significant (p=0.14). The intercanine width, intermolar width, arch length and arch perimeter was greater in males than females. (p<0.001) Conclusions: Sexual dimorphism was observed among the studied dental arch parameters. Dental arch dimensions like intercanine width of the maxillary arch, intermolar width, and arch perimeter of both maxillary and mandibular arches showed to be an indicator for gender determination with an accuracy of 100%.